Nilai Tradisi Bulusan di Desa Hadipolo Kecamatan Jekulo Kabupaten Kudus dan Relevansinya dengan Bimbingan Islam - Alfina Rahmawati; Namira Choirani Fajri; Maryatul Kibtiyah (EMPATI: Jurnal Bimbingan dan Konseling, 2026)
The Bulusan Tradition in Hadipolo Village, Jekulo Subdistrict, Kudus Regency is a local cultural heritage that remains preserved and is rich in religious, social, customary, and moral values. This study is important to examine the values contained in the Bulusan Tradition and its relevance to Islamic Guidance from the perspective of Islamic Guidance and Counseling studies. The research hypothesis is that the Bulusan Tradition aligns with the principles of iman (faith), Islam (practice), and ihsan (excellence), making it relevant as a media for culturally- based Islamic guidance. The study employed a qualitative approach using ethnographic methods through participatory observation, in-depth interviews, and documentation. Data analysis was conducted descriptively-interpretatively using Koentjaraningrat’s cultural theory and Anwar Sutoyo’s Islamic Guidance concept. The results show that the values of the Bulusan Tradition are internalized in seven elements of culture and support the strengthening of faith, social care, and moral development. These findings highlight the importance of the Bulusan Tradition as a medium for cultural da’wah and non-formal Islamic guidance that is contextual and sustainable.